Synaptic vesicle capture by CaV2.2 calcium channels - Wong, Fiona K.; Li, Qi; Stanley, Elise F. (Frontiers in Cellular Neuroscience, 2013)
The fusion of synaptic vesicles (SVs) at the presynaptic transmitter release face is gated by Ca2+ influx from nearby voltage gated calcium channels (CaV). Functional studies favour a direct molecular ‘tethering’ attachment and recent studies have proposed a direct link to the channel C terminal. To test for direct CaV-SV attachment we developed an in vitro assay, termed SV pull down (SV-PD), to test for capture of purified, intact SVs. Antibody-immobilized presynaptic or expressed CaV2.2 channels but not plain beads, IgG or pre-blocked antibody successfully captured SVs, as assessed by Western blot for a variety of protein markers. SV-PD was also observed with terminal fusion proteins of the distal half of the C terminal, supporting involvement of this CaV region in tethering. Thus our results support a model in which the SV tethers directly to the CaV. Since the tip of the C terminal could extend as far as 200 nm into the cytoplasm, we hypothesize that this link may serve as the initial SV capture mechanism by the release site. Further studies will be necessary to evaluate the molecular basis of C terminal tethering and whether the SV binds to the channel by additional, shorter-range attachments.